The Influence of Savings Interest on the Financial Literacy Level of Students at SDN Brengosan 1 - Meilawati, Ridha; Rigianti, Henry Aditia (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2025)
The research aims to find out whether there is an influence between savings interests on the level of financial literacy of students of SD N Brengosan 1. This research was carried out at SD N Brengosan 1 which is rescued at JL. Kayunan Raya No. 3 Kayunan. This research is a quantitative survey using a questionnaire. The sampling technique in this study used random samplings with a total sample of 84 students out of a total population of 106 students. The analytical technique used was a simple regression test continued with a hypothesis test with a degree of significance of 0.05. The results of the study concluded that the simple regression test yielded a positive regression coefficient value which means that interest in saving had a positive influence on financial literacy resulting in a regression equation of Y + 0.581 + 0.911 X. The square R value derived from the determination factor test resulted in a value of 0.704, which means the influence of savings interest on the student's level of financial literature was 70,4% which meant that the individual had knowledge of moderate financial literation.